HUBUNGAN KEMAMPUAN KOMUNIKASI INTERPERSONAL SISWA DENGAN MOTIVASI BELAJAR SISWA KELAS VIII SMP IBNU AQIL KABUPETEN BOGOR - Mawaddah, Zakia (EDUTECH CONSULTANT, 2019)
This study aims to determine whether there is a significant relationship between students 'interpersonal communication skills and students' learning motivation. This type of research is quantitative research. This study has a population of 215 class VIII Ibnu Aqil Middle School Bogor Regency with a sampling technique using Simple Random Sampling as much as 25% of the population, as many as 54 samples. The data collection technique in this study uses a Likert scale questionnaire and the data analysis used is validity test and reliability test with the help of SPSS version 22 program. Based on data obtained and analyzed by Product Moment correlation test there is a relationship between students' interpersonal communication skills and student learning motivation amounting to 0.516 which is at the level of 0.40 - 0.70 which includes MEDIUM or ENOUGH. With a significant value at the level of 5% of 0.266, then r_count (0.516)> r_tabel (0.266) which means the hypothesis (Ha) is accepted.